Oral and gastrointestinal nutrient bioaccessibility of gluten-free bread is slightly affected by deficient mastication in the elderly - Ribes, Susana; Genot, Mélany; Vénien, Annie; Santé-Lhoutellier, Véronique; Peyron, Marie-Agnès (Food research international, 2023)
[Display omitted] •FT-IR tests revealed in situ lower oral starch digestion in impaired masticated boluses.•Gastric protein digestibility was lower in the poorly masticated gluten-free bread tested.•Deficient mastication did not alter protein hydrolysis and sugar release at the end of digestion.•Deficient mastication did not impact on lipid peroxidation at the end of digestion. The main goal of this work was to investigate the impact of impaired mastication on nutrient bioaccessibility of gluten-free bread in the elderly. In vitro boluses were produced with the AM2 masticator by using two types of programming: normal mastication (NM) and deficient mastication (DM). Static in vitro gastrointestinal digestion was performed with the digestive physiology conditions of the elderly. Subsequently, the granulometric properties of the in vitro boluses produced, their starch and protein digestibility, and lipid peroxidation after in vitro oral and gastrointestinal digestion were evaluated. DM boluses presented higher proportions of large particles, resulting in insufficiently fragmented boluses. A delay in oral starch digestion was observed in DM boluses, probably due to the presence of larger particles that limited the bolus-saliva exchanges. Furthermore, DM boluses exhibited a lower degree of protein hydrolysis at the end of gastric digestion, whereas no differences were observed for protein hydrolysis, sugar release, and lipid peroxidation at the end of digestion (intestinal phase). The results of this study show that impaired mastication somewhat delays the nutrient bioaccessibility of the gluten-free bread tested. Such understanding of the effect of oral decline on the nutrient bioaccessibility of foods is crucial when designing food commodities with enhanced functionalities for the elderly.